Risk Assessment of Heavy Metal Toxicity and Stress Marker Enzyme in Waste Water from Municipal Dam Site around Enugu Metropolis, Enugu State - Anikwe, Uchenna, Fredrick; Okenwa, Ezinne Jennifer; Ona, Jekwu, S. E.; Anikwe, Chidera, Henry; Oparaji, Emeka H. (European Journal of Applied Sciences, 2022)
Impact of waste water toxicity from collection ditches within Enugu metropolis, Enugu state was assessed in the present study. Risk impact of heavy metal recalcitrant was also determined in the present study as the waste water from the ditch were used by subsistence farmers around for irrigation purposes. Physicochemical analysis of the soil irrigation with the domestic waste water was carried and revealed the following: pH 6.65, conductivity 792 respectively. Dissolved mineral contents were found in the following order: Cl>Ca>Fe>SO4>Mg>Cu>K>Pb>PO3 while heavy metals of Hg, As and Cd were found at below detectable limit range (BDL). Total organic carbon (TOC) and total organic matter (TOM) contents were found at 179.93 and 221 mg/kg in the various treatments. These varied significantly from the control treatment. Physicochemical properties of the domestic waste water were equally analyzed. Soil enzymes showed the activity of the lipase, urease, peroxidase and catalase with an increased of lipase, urease and peroxidase after the irrigation with OD of 0.610, 0.677 and 0.712 respectively catalase activity was reduced downwardly. Health risks to human through utilization of the waste water by human were assessed by: estimated dietary intake (EDI), estimated weekly intake (EWI) and Target hazard quotient (THQ). EDI for the heavy metals of Pb, Cu and Fe were 3.98 x 10-3, 1.22 x 10-2 and 1.2 x 10-2 mg/g, respectively estimated while EDI of 1.36 x 10-3, 8.33 x 10-3 and 9.52 x 10-3 mg/g were obtained for Pb, Cu and Fe from the control experiments. EWI for heavy metals of Pb, Cu and Fe were 9.52 x 10-3, 583 x 10-2 and 6.7 x 10-2 mg/g, respectively. The results showed that the THQ for Fe and Cu were less than 1 while that of Pb was greater than 1. THQ were less than 1in all the analysed metals from the control experiment. The findings from this study show that there is a considerable health risks connected with utilization of waste water from our study locale and these waste water bioaccumulate heavy metal levels which are potentially poisonous to humans who consume them.